The Influence of Airline Ticket Price Reduction Policy and Tourist Consumption Behavior on Year-End Holiday Destination Choices in Indonesia - Abas, Sofyan; Priyana, Yana; Arini, Rani Eka (West Science Interdisciplinary Studies, 2025)
This study examines the impact of airline ticket price reduction policies and tourist consumption behavior on the choice of year-end holiday destinations in Indonesia. A quantitative approach was employed, involving 60 respondents selected through purposive sampling. Data were collected via a structured questionnaire using a Likert scale (1-5) and analyzed with SPSS version 25. The findings reveal that both airline ticket price reduction policies and tourist consumption behavior significantly influence destination choices, with price reduction policies having a stronger effect. The regression model explains 63% of the variance in destination choices, highlighting the importance of affordability and spending preferences in shaping travel decisions. These results provide valuable insights for policymakers and tourism stakeholders to design strategies that enhance destination competitiveness, particularly during peak travel seasons.